Malaria vaccine: roadblocks and possible solutions - Soares,I.S. (1998)
Malaria remains the most prevalent and devastating parasitic disease worldwide. Vaccination is considered to be an approach that will complement other strategies for prevention and control of the disease in the future. In the last 10 years, intense studies aimed at the development of a malaria vaccine have provided important knowledge of the nature of the host immunological mechanisms of protection and their respective target antigens. It became well established that protective immune responses can be generated against the distinct stages of Plasmodium. However, in general, protective immune responses are directed at stage-specific antigens. The elucidation of the primary structure of these antigens made possible the generation of synthetic and recombinant proteins that are being extensively used in experimental immunizations against the infection. Today, several epitopes of limited polymorphism have been described and protective immunity can be generated by immunization with them. These epitopes are being tested as primary candidates for a subunit vaccine against malaria. Here we critically review the major roadblocks for the development of a malaria vaccine and provide some insight on how these problems are being solved